ICT dynamics for gender inclusive intermediary education: Minimum poverty and inequality thresholds in developing countries - Simplice Asongu; Mouna Amari; Anis Jarboui; Khaireddine Mouakhar (African Governance and Development Institute (AGDI), 2021)
This study examines linkages between information and communication technology (ICT) dynamics, inequality and poverty in order to establish critical masses of poverty and inequality that should not be exceeded in order for ICT dynamics to promote gender inclusive education in 57 developing countries for the period 2012-2016. Poverty is measured with the poverty headcount ratio at national poverty lines (% of the population) while inequality is proxied by the Gini coefficient, the Atkinson index and the Palma ratio. The ICT dynamics are measured with 'internet access in school', 'virtual social network', 'personal computers' 'mobile phone penetration', 'internet penetration' and 'fixed broadband subscriptions'. The empirical evidence is based on interactive Generalized Method of Moments estimators from which thresholds are computed contingent on the validity of tested hypotheses. First, the Gini coefficient should not exceed 0.5618 in order for 'internet access in school' to positively affect inclusive education. Second, the poverty headcount ratio at national poverty lines (% of the population) should remain below 33.6842% in order for 'internet access in school' to favorably influence inclusive education. Third, the Palma ratio should not exceed 3.3766 in order for internet penetration to favorably affect inclusive education. Fourth, for personal computers to increase inclusive education, the Gini coefficient, Palma ratio and poverty headcount (% of the population) should not exceed 0.4781, 3.5294 and 17.7272, respectively. The study confirms the significant role technological deepening plays in advancing inclusive education by means of policies that reduce poverty and income inequality, with potentially wider applicability to other developing economies. The study has provided poverty and inequality levels that should not be exceeded in order for personal computers, internet penetration and 'internet access in school' to promote gender inclusive education.
Keywords: 330; Inclusive; Education; Inequality; Technology; Thresholds